Security Challenges and Women Political Participation in 2019 General Elections in Nigeria: A Bird’s Eye View - UFERE–OKORAFOR, Uche; OSHINFOWOKAN, Oluseyi; NWANEGBO, C. Jaja (Socialscientia: Journal of Social Sciences and Humanities, 2021)
Election security is a key consideration in structuring electoral process and for smooth and robust participation in elections. The 2019 general elections were conducted amidst various security threats. As in the previous elections, cases of electoral insecurity such as killing, maiming, intimidation, molestation, hijacking of electoral materials, interferences by security agents and systematic manipulation of the party’s structure which played out in favour of men were observed in the build-up and during the elections. Again, despite the fact that the age long known predicaments that engender discriminatory acts against women’s full participation in politics appear unresolved, new and frightening challenges, especially in the area of security emerged. With it is the record of drops in women’s participation in politics to unacceptable level in the face of increased women representation in many other countries of the world. It is against this backdrop that this paper takes a bird eye view on the implications of the spate of insecurity during the elections on the participation of women and their emergence into the elected and policy making positions in the 2019 general elections in Nigeria. Employing descriptive model of electoral violence, the paper argues that the quest by women to actualize 35% affirmative right action is hindered by the rise in militarization of the electoral process by the men. Through organized and established violence in elections and the failure of the security community to police the elections in Nigeria, many women were scared away always from participating actively in the electoral processes, thereby, leading to under-representation of women in elective positions. The paper recommends the use of legislation to regulate arbitrary conducts that creates insecurity in our elections, regulate the misuse of security personnel for the attainment of proportional representation in Nigeria; and amendment of Electoral Act to provide for strict punishment for electoral violence and offenders.